An Old Hebrew Romance of Alexander as One of the Sources for the "Conversion of K’art’li" - Constantine B. Lerner (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
A Romance of Alexander Mucdon (Macedon) was created in Hebrew, ni the 2m-3rd .c A. D,. representing a legendary reflection of the Caucasian campaign of Pompey as it is described in the works by Duo Casius and Appian. In the Romance the invasion of Iberia by Pompey (in 65 B. C.) appears as the 'march of Alexander ot the land of Afriqi'. Later the "Romance" served as one of the sources for the Georgian chronicle "The Conversion of K'art'li" (Mok'c'evay K'art'lisay) and the story of Alexander in such confused form entered ancient Georgian historiography as a story about Alexander's invasion of K'art li. In the "Romance" the main names of the kings of K'art'li are: Azo(n) and Arik. The Hebrew "Romance" contains also the legendary description of two other episodes concerning the battle in Armazi and supposed march of Pompey to Colchis (Egrisi).